(untitled) (Research, Society and Development, 2021)
Generation Z is defined in the social environment as the technological generation, which includes those born between the years 1995 and 2010, little is said about this generation when referring to diseases, since for all pathologies there is already scientific knowledge, but because it is of such a technological generation, it is not known whether these young people are so aware of the risks. The general objective of this research is to portray the relationship between generation Z and the resurgence of STIs already eradicated and with emerging ones, in addition to reporting the role of parents in today’s society. As a research method, an analysis of the descriptive bibliographic literature was carried out, articles from the health sciences area were selected. Finally, it is concluded with this research that knowing technology is not enough if it is not used correctly, and sexual health is more important than any other means when it comes to reducing STI positive cases.